Mutational spectrum of PTS gene and in silico pathological assessment of a novel variant in Mexico - Fernández-Lainez, Cynthia; Ibarra-González, Isabel; Alcántara-Ortigoza, Miguel Ángel; Fernández-Hernández, Liliana; Enríquez-Flores, Sergio; González-del Ángel, Ariadna; Blau, Nenad; Thöny, Beat; Guillén-López, Sara; Belmont-Martínez, Leticia; Ruiz-García, Matilde; Vela-Amieva, Marcela (Brain & development, 2018)
Background - Tetrahydrobiopterin (BH4) is the cofactor for 6-pyruvoyl-tetrahydropterin synthase (PTPS); it is involved in BH4 biosynthesis and is encoded by PTS gene. Its deficiency (PTPSD) is characterized by hyperphenylalaninemia (HPA) and deficit in central monoamine neurotransmitters. We describe the clinical and mutational spectrum of five patients with PTPSD, from four unrelated Mexican families. All patients had symptomatic diagnosis and presented severe early neurological manifestations and HPA. - Methods - Clinical and biochemical data from studied patients were recorded. Responsible PTPSD genotypes was determined by direct and bidirectional Sanger DNA sequencing of the six PTS coding exons and their exon-intron borders, and these were directly searched in the available relatives. The novel PTS missense variant [NM_3000317.2:331G>T, p.(Ala111Ser)] was subjected to in silico, to predict a possible deleterious effect. - Results - Diminished fetal movements were perceived as a uniform characteristic in the studied group. DNA sequencing showed two known p.(Arg25∗) and p.(Val132TyrFs∗19) and the novel missense p.(Ala111Ser) PTS variants, the latter representing potentially a frequent PTPSD-responsible allele (50%, 4/8) in Mexican patients. In silico protein modeling analysis of the p.(Ala111Ser) variant revealed loss of hydrophobic interactions between the alanine and neighboring valines, suggesting that these changes in polarity may be detrimental for enzyme function, structure and/or stability. - Conclusions - This work contributes to the knowledge of PTPS molecular spectrum. The delayed diagnosis of these patients emphasizes the importance of considering BH4 metabolism defects in the differential diagnosis of HPA, especially for countries that are beginning their HPA newborn screening programs.
Gesehen am 13.05.2020